Correlation between the proportion of healthy mammary tissue versus tumor size in breast-conserving surgeries - Pinson, Gabriela Grando; Pacheco, Julianes; Bertuol Júnior, Vanderlei Carlos; Vivian, Fernando (Mastology, 2020)
Objective: To evaluate the proportion of excised healthy tissue in breast-conserving surgeries and to identify possible tendency toward excision in healthy tissue beyond the ideal for oncological safety. Methods: Data from patients who underwent breast-conserving surgery at the Hospital Geral de Caxias do Sul from January 2010 to December 2016 were analyzed. For statistical purposes, means, standard deviations, Student’s t-test, and linear regression were used for numerical variables. Risk estimate by odds ratio (OR) was performed through logistic regression with 95% CI. A significance level (alpha) of 5% was adopted. Results: A total of 124 cases were analyzed. The mean tumor size observed by ultrasonography was 1.7 ± 0.95 cm. The tumor size was 1.9 ± 1.12 cm. The mean size of the resected surgical specimens was 7.8 ± 3.4cm. When comparing the tumor size in the anatomopathological examination and the size in ultrasonography, the mean differences accounted for 0.6 cm (95%CI -0.10–0.44; p = 0.2). Conversely, the difference in the size of the total surgical specimen versus tumor size in the anatomopathological examination was 5.8 cm (95%CI 5.2–6.5; p < 0.001). There was no statistical difference regarding the tumor location nor size of the surgical specimen. Conclusion: It was observed that there is a tendency toward excising a large amount of healthy tissue in breast-conserving surgeries far beyond what is recommended in order to consider the oncological safety of excised margins.